¿Los medios de comunicación en Colombia son una industria creadora de valor? (2013)
This article aims to examine whether the media sector in Colombia creates value. For that, an analysis of the financial performance for the period 2006-2011 is made using financial indicators that assess growth, efficiency, effectiveness, efficiency, economic value added, and market value added of this sector. It is found that this sector only creates value in one of the six years of study, showing a high dependence on the effectiveness with which the sector has managed administrative expenses and adjusting its capital structure in order to achieve a lower cost of capital.